The crystal structure of (E)–N-(4-chlorobenzylidene)(4-chlorophenyl)methanamine, C14H11Cl2N - Kong Hanzhu; Ji Yangling; Jin Shouwen; Guo Ming (Zeitschrift für Kristallographie - New Crystal Structures)
C14H11Cl2N, orthorhombic, Pbca, a = 14.5131(13) Å, b = 5.9090(5) Å, c = 29.470(3) Å, V = 2527.3(4) Å3, Z = 8, R gt (F) = 0.0825, wR ref (F 2) = 0.1401, T = 298 K.